Etude D’un Espace Marchand Specialise Dans La Vente De Medicaments De La Rue: L’exemple Du Marche De Roxy A Adjame (Abidjan, Cote d’Ivoire) - Ferrand, Koffi Bouadi Arnaud; Jérôme, Aloko-N'guessan (European Scientific Journal, ESJ, 2017)
This study which has been held on the Roxy market of Adjamé took place from November 2013 to October 2014. It is a transversal study with descriptive and analytical aim whose objective is to proceed to the description of the organization of the circuit of the informal sale of drugs in Abidjan. This article describes the socio-demographic characteristics of street drugs vendors before examining drug pricing methods. Documentary research, direct observation and interviews with vendors were the main techniques used to gatherg information. Our investigations show that the sale of drugs at Roxy is done at 95% by Ivorian women in majority and for the most part illiterate. Pricing is highly dependent on the place of supply of drugs: drugs with a marketing authorization are more expensive on the illicit market than drugs which do not have marketing authorization. In the category of drug products with a marketing authorization: syrups, out-of-stock drugs products in pharmacy and drug the delivery of which asks for time of wait of at least a day in pharmacy is more expensive on the illicit market.